The Long-Term Deep Loessal Sediments of Northeast China: Loess or Loessal Paleosols? - Zhong-Xiu Sun; Nai-Wen Zhang; Ying-Ying Jiang; Qiu-Bing Wang; Gan-Lin Zhang (Quaternary, 2023)
Previous research assumed deep buried loess as the initial composition of the overlying paleosol and failed to address the long-term continuous pedogenic weathering history in the deep loess-paleosol sequence, which was attributed to little understanding on the difference between loess and paleosol in the long-term deep loess-paleosol sequence. To distinguish between the loess and paleosol, in the long-term deep loess-paleosol sequence in northeast China, the morphology, dust deposition fluxes, geochemical characteristics, magnetic susceptibility, and grain size distributions were investigated. Results showed that the loess layers buried at depth could be differentiated from the paleosol by their poor pedogenic development. The presence of coarser grains in the loess as well as lesser amounts of clay and Fe–Mn coatings compared to paleosol indicated weaker weathering of the loess. Also, optical iron clay films deposited on the surface of the skeleton particles were less visible in the loesses than in the paleosols. From the loess evolution perspective, the pedogenic formation process of the newly formed loess soils should be considered as important as that of the reddish paleosol layer based on criteria of formation time, depth within profile, and morphological characteristics. The formation of the reddish or yellowish paleosol layer was constrained by pedogenic environments associated with climatic change and by the relative rates of deposition and pedogenesis. The terms “loessal paleosol” and “loessal paleosol sequence” are suggested to aid in systematically and consistently addressing the long-term pedogenic weathering evolution recorded in the complex formation of deep loess and paleosol sequences in pedology research. The long-term deep loessal sediments of Northeast China are loessal paleosols, which cannot be simply used as a reference for the overlying paleosol and be deducted from pedogenesis consideration.